The Effectiveness of Merdeka Mengajar Platform towards the Learning of English Reading Comprehension as the Implementation of Independent Curriculum at UPTD SMPN 19 Barru - Hijriani Hijriani; Amaluddin Amaluddin; Siti Hajar Larekeng (Journal of English Language Teaching and Literature)
This research aims to find out students' reading comprehension abilities before and after being taught using the Merdeka Menagajar Platform. This study used a one-group pretest-posttest design. There isn't any control group. Researchers give pre-tests to students, and then researchers give students treatment of reading comprehension using the Merdeka Mengajar Platform. The sample of this research was seventh-grade students of UPTD SMPN 19 Barru, a total of 21 students. The results show that the average pre-test score of seventh-grade students at UPTD SMPN 19 Barru experienced a significant increase in the post-test after being taught using the Merdeka Mengajar Platform on treatment. The average student score in reading comprehension on the pre-test was 55.00 and on the post-test was 84.29. So there is an increase in students' reading comprehension.  This study shows the value of the t-test is higher than t-table values (14,496 >2.09302). The results of the t-test calculation of student learning before and after being taught using the Merdeka Mengajar platform are greater than the t-table. Can it be concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted? Researchers concluded that the use of the Merdeka Mengajar platform is a learning method that can improve reading comprehension ability in learning English.